Cross-sectional association of light sensor-measured time outdoors with physical activity and gross motor competency among U.S. preschool-aged children: the 2012 NHANES National Youth Fitness Survey - Soyang Kwon; Pooja S. Tandon; Meghan E. O’Neill; Adam B. Becker (BMC Public Health, 2022)
Abstract Background Time spent outdoors (outdoor time) has been suggested to be beneficial for physical activity (PA) and healthy development among preschool-aged children. The aim of this study was to quantify PA level and gross motor competency associated with light sensor-measured daily outdoor time in a representative sample of U.S. children aged 3 to 5 years. Methods The study sample included 301 participants (149 girls) aged 3 to 5 years from the 2012 U.S. National Health and Examination Survey National Youth Fitness Survey. ActiGraph GT3X+ accelerometers with a built-in ambient light sensor were used to measure PA (expressed in monitor-independent movement summary [MIMS]) and outdoor time. The Test of Gross Motor Development-Second Edition (TGMD-2) was used to assess gross motor skills. Multivariable linear regression models were fit to predict daily and gross motor scores by daily outdoor time. Results Average daily outdoor time was 95 min (median of 84 min; interquartile range of 52 to 123 min). Means of daily outdoor time and daily MIMS were not significantly different between boys and girls. Among girls, every additional 10 min of daily outdoor time was associated with an additional 540 daily total MIMS (95% CI = 372, 708). Among boys, every additional 10 min of daily outdoor time was associated with an additional 296 daily total MIMS (95% CI = 131, 460). Every additional 10 min of daily outdoor time was associated with a 0.1-point (95% CI = 0.001, 0.130) higher object control standard score. Daily outdoor time was not associated with a locomotor standard score. Conclusions In a representative sample of U.S. preschool-aged children, daily outdoor time was positively associated with daily PA. The contribution of outdoor time to PA was greater among girls than boys, suggesting that providing outdoor opportunities is critical for promoting PA, particularly among girls.